2016
DOI: 10.1111/acem.13033
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Elevated Cardiac Troponins in the Emergency Department and Their Associated Mortality

Abstract: Of all ED patients with elevated cTn, ~75% have a non-T1MI. The mortality of patients with non-T1MI is similar to the mortality in patients with T1MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 25 publications
1
53
0
Order By: Relevance
“…PLWH are at higher risk of myocardial infarction (MI) compared to the general population (10). Recent work has shown that among PLWH approximately half of incident MIs are Type 2 MI (T2MI) (11), whereas in the general population T2MI accounts for a much smaller proportion of MIs (12)(13)(14)(15)(16)(17)(18)(19)(20). In contrast to classical atheroembolic Type 1 MI (T1MI), T2MI results from myocardial oxygen demand-supply mismatch, a scenario that may result from a variety of conditions, including sepsis, illegal stimulant or drug-induced vasospasm, decompensated heart failure, and hypotension (21).…”
Section: Word Count: 2736 Wordsmentioning
confidence: 99%
“…PLWH are at higher risk of myocardial infarction (MI) compared to the general population (10). Recent work has shown that among PLWH approximately half of incident MIs are Type 2 MI (T2MI) (11), whereas in the general population T2MI accounts for a much smaller proportion of MIs (12)(13)(14)(15)(16)(17)(18)(19)(20). In contrast to classical atheroembolic Type 1 MI (T1MI), T2MI results from myocardial oxygen demand-supply mismatch, a scenario that may result from a variety of conditions, including sepsis, illegal stimulant or drug-induced vasospasm, decompensated heart failure, and hypotension (21).…”
Section: Word Count: 2736 Wordsmentioning
confidence: 99%
“…Patients were placed in 1 of 5 clinical groupings after review of all available medical records pertaining to the patient from ED presentation to 30-day follow-up. The first group included those with AMI, diagnosed according to the universal definition of AMI (Thygesen et al 2012, Meigher et al 2016. The s-cTnI assay was used for this adjudication (the ED physicians did not have access to these values) and there was complete blinding to hs-cTnT levels during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Troponin measurements are commonly ordered in US EDs (14% of patients) and all abnormal values reported are those above the 99th %.value for the contemporary assays currently utilized (Meigher et al 2016). However, emergency physicians in the US will be seeing in the future very low hscTnT measurements (<99th %) reported, mostly in those patients who have been ruled out for ACS (the vast majority of those evaluated).…”
Section: Contextmentioning
confidence: 99%
“…Saaby et al proposed stringent criteria that required the presence of one of the following clinical features to meet the diagnosis: (1) severe anemia defined as hemoglobin <5.5, (2) shock defined as systolic blood pressure <90 mmHg together with signs of organ dysfunction (i.e., metabolic acidosis, arterial oxygen tension <8 kPa, oliguria [diuresis <30 mL/h for at least 3 h], or encephalopathy), (3) bradyarrhythmias requiring medical treatment or pacing, (4) coronary embolism in the presence of a vegetation or ventricular thrombus, (5) respiratory failure with an arterial oxygen tension <8 kPa and clinical signs of acute respiratory failure lasting ≥20 min, (6) ventricular tachyarrhythmia lasting ≥20 min, (7) supraventricular tachycardia lasting ≥20 min with a ventricular rate >150 beats/min, (8) hypertensive pulmonary edema defined as the presence of a systolic blood pressure >160 mmHg, signs of pulmonary edema, and a need for treatment with nitrates or diuretics, or (9) arterial hypertension with systolic blood pressure >160 mmHg and concomitant left ventricular hypertrophy identified by echocardiography or ECG. 11, 12 In contrast, Sandoval et al 13 proposed the necessity of acute or sustained supply/demand imbalance in the absence of other underlying conditions that lower the ischemic 25 However the investigators state that a further 35.7% of patients with elevated troponin were "multifactorial" and 2.5% were due to non-ischemic myocardial injury. 25 The large proportion of multifactorial troponin elevations reported by those authors limits our interpretation of their results.…”
Section: Definitionmentioning
confidence: 99%
“…11, 12 In contrast, Sandoval et al 13 proposed the necessity of acute or sustained supply/demand imbalance in the absence of other underlying conditions that lower the ischemic 25 However the investigators state that a further 35.7% of patients with elevated troponin were "multifactorial" and 2.5% were due to non-ischemic myocardial injury. 25 The large proportion of multifactorial troponin elevations reported by those authors limits our interpretation of their results. Smith et al 26 examined the incidence of T2MI in 662 patients presenting to the ED with symptoms of ischemia; 139 patients were adjudicated to have a MI, with T2MI comprising 71% of this cohort.…”
Section: Definitionmentioning
confidence: 99%